PENGARUH BESAR ARUS LISTRIK DENGAN MENGGUNAKAN ELEKTRODA SMAW TERHADAP KEKUATAN SAMBUNGAN LAS BUTT JOINT PADA PLAT MILD STEEL - Jokosisworo, Sarjito (Kapal: Jurnal Ilmu Pengetahuan dan Teknologi Kelautan, 2009)
The influence of mechanic disposition, is one of the factor influence ship strength. This influence can be test by mechanical test in welding butt joint. The result test database analysis can be conclude that very helpful to increase safety and quality butt joint. With steel specification C= 0,15%, Si= 0,24%, Mn= 0,88%,P= 0,018%, S= 0,034%. This material give a 90, 110, 125 ampere with SMAW AC electrode diameter 3,2 mm x 350 mm with V root and 600 angle In the fabrication of mild steel products, components or equipment, manufacturers employ welding as the principal joining method. Mild steel are weldable materials, and a welded joint can provide optimum corrosion resistance, strength, and fabrication economy. However, designers should recognize that any metal, including stainless steels, may undergo certain changes during welding. It is necessary, therefore, to exercise a reasonable degree of care during welding to minimize or prevent any deleterious effects that may occur, and to preserve the same degree of corrosion resistance and strength in weld zone that is an intheren part of the base metal